2013
DOI: 10.5772/55607
|View full text |Cite
|
Sign up to set email alerts
|

Robot Emotion and Performance Regulation Based on HMM

Abstract: This paper discusses the transference process of emotional states driven by psychological energy in the active field state space and also builds a robot expression model based on the Hidden Marov Models(HMM). Facial expressions and behaviours are two important channels for human‐robot interaction. Robot performance based on a static emotional state cannot vividly display dynamic and complex emotional transference. Building a real‐time emotional interactive model is a critical part of robot expression. First, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Hand-coded robotic animations can offer high quality [175]. However, these static approaches are limited because "robot performance based on a static emotional state cannot vividly display dynamic and complex emotional transference" ( [282], p. 160). Furthermore, the limited set of emotions increases the likelihood of repetitive behavior, which may appear inappropriate in HRI.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Hand-coded robotic animations can offer high quality [175]. However, these static approaches are limited because "robot performance based on a static emotional state cannot vividly display dynamic and complex emotional transference" ( [282], p. 160). Furthermore, the limited set of emotions increases the likelihood of repetitive behavior, which may appear inappropriate in HRI.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…In 0-15 s, robot's own emotion remained about the same under no external stimulus. At the 15 s, an external stimulus "disgust" derived from microexpression occurred, so robot emotion's negative degree gradually increased during 15-35 s and achieved the balance around the 35 s. Then this emotional experience was with the robot for about 15 s. Because the "disgust" stimulus has disappeared a while, robot emotional state gradually trended to "calming" during 50-65 s [30]. At the 65 s, an Filtered 34 volunteers participate in the human-robot interactions and each person experiments 100-time interaction in accordance with specified criteria.…”
Section: Emotional Regulation Processmentioning
confidence: 99%
“…But the obtained results are difficult to compare with other emotional regulation studies that can be found in literature, because most of such studies do not recognize stimulus emotions in microexpressions and transfer emotional states in arousal-valence-stance terms. Moreover the few studies that do have not been tested under physical robot experimental conditions (specific robot device and experimental platform refer to [30,31]) and do not provide as output the coordinates of the studied emotional state in the 3D space.…”
Section: Emotional Regulation Processmentioning
confidence: 99%
“…Behavioral expression is a random process of emotional expression after psychological experience generated. The two kinds of random process are in line with HMM, and thus we can use it to describe Gross' process model of emotion regulation in a mathematical method [5,11]. HMM is a statistical probability model including hidden states and Markov chain that is represented by parameters.…”
Section: Gross' Emotion Regulation Model Based On Hmmmentioning
confidence: 99%